The aesthetics of composition in the epic theatrical scene Al-Mutanabbi is a model (Journal of the College of Basic Education, 2023)
The theater has undergone many transformations and changes due to the ages, whether in its building, stage, presentation of topics, decor, directing style, or acting style.The theatrical show is that artistic painting consisting of a group of aesthetic images due to the aesthetic elements of line, mass, rhythm, color, supremacy, unity, balance, etc. Through these elements, those artistic images are formed, which are the creations of the director, the vision of the designer, and the talent of the actor in embodying the role.The expression of the artistic image differs according to the nature of the variables involved in the process of building a variety of forms and artistic trends, and for the purpose of standing on the importance of composition in theatrical performance, the research came in four chapters:The first chapter: came as a representative of the methodological framework, which included the presentation of the research problem, its importance and objectives, and the definition of terminology.The second chapter: The theoretical framework included two sections:The first topic: the elements of aesthetic composition.The second topic: the mechanisms of functioning of the formation elements in the epic theatrical scene.Then come up with theoretical framework indicators.Chapter Three: The research community, research methodology, and analysis of the research sample were identified.Chapter Four: It included the presentation of the research results, and then concluded the research with an English language summary and a list of sources and references.